Intensitas menonton vlog Kemal Palevi dan Persepsi tentang vlog Kemal Palevi dengan Sikap melakukan Cyberbullying pada Kemal Palevi melalui media social - Yosua, Christian; Nur Suryanto Gono, Joyo (Interaksi Online, 2018)
In this modern age the world has undergone rapid development. technological progress is one of the most visible advances. The most widespread form in use by the world community is the internet. But technological progress can not be separated also from the problems brought about by these technological advances as well. Cyberbullying is a problem that comes along with the technological advances. The modern version of this breeding becomes a problem that plagues and even casualties. The purpose of this research is to know the relationship of watching intencity Kemal Palevi’s vlog and perception about Kemal Palevi’s vlog with Attitude to cyberbullying on Kemal Palevi. The population of this research is teen millenials from 17 - 34 years old by using purposive sampling technique. Based on the test performed using the Chi-Square formula, it shows the result that: first, the intensity of watching the vlog of Kemal Palevi with attitude of cyberbullying on Kemal Palevi with asymptotic significance value of 0.000, but there are 4 cells with expectation value below 5 (50% 20%) and the lowest expectation value is 2.52. thus the hypothesis can not be inferred. Secondly, there is a positive correlation between perception of Kemal Palevi vlog with cyberbullying attitude on Kemal Palevi with significance value 0, but there are 4 cells with expectation value below 5 (50%> 20%) and lowest expectation value 1.80. Thus the hypothesis can not be concluded. suggestions given that Kemal Palevi should create a text or subtitle in the vlog that contains a foreign language so that the audience can absorb the information and the message as a whole from the vlog he watched.